Analysis of noncatheter-associated upper extremity deep venous thrombosis from the RIETE registry - Newton DH; Monreal Bosch M; Amendola M; Wolfe L; Perez Ductor C; Lecumberri R; Levy MM; RIETE Investigators.; Bosevski M; Zdraveska M (Elsevier, 2017)
Objective: We sought to determine the risk factors for subsequent bleeding and recurrent venous thromboembolism (VTE) events following isolated noncatheter-associated upper extremity deep venous thrombosis (non-CA-UEDVT) to better inform future treatment decisions for this group of patients. Methods: The RIETE registry (Registro Informatizado de Enfermedad TromboEmbólica [Computerized Registry of Patients with Venous Thromboembolism]) is a prospective international registry of patients with objectively confirmed symptomatic VTE. Patients with a symptomatic, isolated, proximal UEDVT from March 2001 through March 2015 were analyzed. Any patient with an indwelling catheter or pacemaker lead at the DVT site and at the time of thrombosis was considered to have a CA-UEDVT and was excluded. Patient and treatment characteristics such as age, gender, comorbidities, VTE risk factors, treatment drug, and duration were collected. Outcomes examined included recurrent DVT, subsequent pulmonary embolism (PE), and hemorrhage. Multivariate analysis was performed using stepwise logistic regression. Results: Of the 1100 patients who met the study criteria, 580 (53%) were male. The mean age of the patients was 50 ± 20 years, and overall patient survival at 1 year was 85%. Recurrent VTE occurred in 59 patients (5.4%). Of these, 46 patients (4%) had recurrent DVT, 10 (0.9%) had a PE following UEDVT diagnosis, and 3 (0.3%) had both. PE was fatal in three patients (0.3%). Bleeding occurred in 50 patients (4.5%), major bleeding in 19 patients (1.7%), and fatal bleeding in 6 patients (0.5%). On multivariate analysis, malignant disease was associated with VTE recurrence (odds ratio [OR], 2.00; 95% confidence interval [CI], 1.04-3.45; P < .04), whereas hemorrhage was associated with age (OR, 1.03; 95% CI, 1.01-1.05; P = .002) and malignant disease (OR, 2.53; 95% CI, 1.34-4.76; P < .005). Hemorrhage and recurrent VTE were also significantly associated (OR, 2.79; 95% CI, 1.16-6.76; P < .03). Conclusions: PE following non-CA-UEDVT is rare. Malignant disease was associated with VTE recurrence. Age and malignant disease were associated with hemorrhage, and VTE recurrence was associated with hemorrhage. Further prospective studies should be undertaken to best determine length of anticoagulation treatment for the varied populations of patients with UEDVT.